2018
DOI: 10.1089/thy.2017.0330
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyrotropin on Peripheral Thyroid Hormone Metabolism and Serum Lipids

Abstract: TSH has direct effects on peripheral TH metabolism by decreasing T3 levels in levothyroxine-treated thyroidectomized patients. This decrease in T3 levels is accompanied by unfavorable changes in serum lipids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…A recent study reported the effect of rhTSH on 82 patients with differentiated thyroid cancer, previously treated with total thyroidectomy and 131 I remnant ablation [26]. The analyses showed a decrease of HDL, from 0.92 to 0.81 mmol/L (p < 0.001), and increase of triglycerides from 1.98 to 2.50 mmol/L (p < 0.001), both associated with the decrease of T3 level.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study reported the effect of rhTSH on 82 patients with differentiated thyroid cancer, previously treated with total thyroidectomy and 131 I remnant ablation [26]. The analyses showed a decrease of HDL, from 0.92 to 0.81 mmol/L (p < 0.001), and increase of triglycerides from 1.98 to 2.50 mmol/L (p < 0.001), both associated with the decrease of T3 level.…”
Section: Discussionmentioning
confidence: 97%
“…In this context, TSH directly increased lipogenesis by activating SREBP1c via a cAMP/PKA/PPARα signaling pathway associated with AMPK in hepatic cells (101). Recently, it was shown that the administration of recombinant human TSH increases serum apoB, Lp(a), non-HDL cholesterol, and TAGs in patients after thyroidectomy on a stable dose of LT4 (102). After TSH administration, T3 levels were reduced and changes in lipids were inversely associated with the T3 levels, suggesting that TSH may have had an indirect effect on lipid levels (102), perhaps due to effects on the deiodinase activity.…”
Section: Tsh and Lipid Metabolismmentioning
confidence: 99%
“…Of note, given that progression of the disease is accompanied by significantly decreased nitrite and nitrate levels, nitric oxide (NO) levels could be a reliable biomarker for cardiovascular risk in SCH ( 77 ). Recently, a retrospective analysis of 82 thyroidectomized patients with differentiated thyroid cancer showed that following stimulation by recombinant human TSH (rhTSH), serum T3 concentrations decreased (from 1.91 to 1.81 nmol/L; p < 0.001), while T4, fT4, and rT3 remained unchanged ( 78 ). Thus, these results may suggest that TSH has a direct effect on peripheral TH metabolism by decreasing T3 in patients receiving L-T4 and that the decline in T3 may cause the dyslipidemic profile.…”
Section: Treatment With L-t4: Why Who and Howmentioning
confidence: 99%